Agro-physical assessment of different pea (Pisum sativum) cultivars in lowland rice (Oryza sativa) fallow under no-till system for enhancing cropping intensity and productivity in mid hills of northeast India - DAS, ANUP; CHOWDHURY, SAMIK; LAYEK, JAYANTA; I, RAMKRUSHNA G; PANWAR, A S; NGACHAN, S V; BURAGOHAIN, JURI (The Indian Journal of Agricultural Sciences, 2017)
The cropping intensity of North Eastern Region (NER) of India is low (134%) mainly due to non-utilization of fallow lands after harvesting of rainy season rice (Oryza sativa L.). Pea (Pisum sativum L.) is one of the most potential leguminous field crops for crop diversification and enhancing productivity of rice based cropping systems in NER. Thus, a field experiment was conducted during 2012-13 and 2013-14 to evaluate the performance of pea cultivars under no-till (NT) condition after harvest of lowland rice in mid-hills (Umiam, Meghalaya, 950 m above sea level, 25°30’N latitude and 91°51’E longitude) of North East India.Twenty one pea cultivars were tested in rice fallow conditions under NT with the residual soil moisture. Out of 21 genotypes, 11 were pole type (PT) and 10 were dwarf type (DT). Among the cultivars, Arkel (95 days) followed by IPFD 4-6 (129 days) and IPFD 1-01 (130 days) were the most early maturing, and IPF 14 (150 days) and IPF 2-13 (150 days) were the most late maturing genotypes. Among all the cultivars, leaf area index, chlorophyll index, number of nodules/plant and nodule weight/plant were higher in Arkel among PT and IPFD 4-6 among DT cultivars. Among all PT cultivars, the higher seed yield, crude protein and total P content was recorded in Arkel (2.37 t/ha, 23.4% and 0.94%), VL-42 (2.33 t/ha, 23.2% and 0.91%) and MUD P 15 (2.29 t/ha, 22.3% and 0.84%); while among DT cultivars, these values were higher in IPFD 4-6 (2.25 t/ha, 20.7% and 0.75%), IPFD 1-01 (2.23 t/ha, 20.6% and 0.72%) and IPFD 99-13 (2.18 t/ha, 20.1% and 0.69%, respectively) than others. Aphid and rust were the most prominent insect and disease, respectively. Among PT cultivars, IPF 99-26 followed by MUD P 15 and among DT cultivars, Prakash and IPFD 5-10 showed maximum resistance against pea aphid. VL-42 was the most disease resistant variety followed by Arkel among the PT and Vikash followed by IPFD 99-13 among the DT cultivars. Thus, the study revealed the opportunity of pea cultivation in lowland rice fallow with suitable cultivars and appropriate technologies in mid-altitude of Meghalaya.